Activated phosphoinositde 3-kinase (PI3Kδ) syndrome: an Italian point of view on diagnosis and new advances in treatment - Vassilios Lougaris; Federico Le Piane; Caterina Cancrini; Francesca Conti; Alberto Tommasini; Raffaele Badolato; Antonino Trizzino; Marco Zecca; Antonio De Rosa; Federica Barzaghi; Claudio Pignata (BMC, 2024)
Abstract Activated phosphoinositide 3-kinase (PI3Kδ) Syndrome (APDS) is an inborn error of immunity (IEI) with a variable clinical presentation, characterized by infection susceptibility and immune dysregulation that may overlaps with other Primary Immune Regulatory Disorders (PIRDs). The rarity of the disease, its recent discovery, and the multiform /multifaced clinical presentation make it difficult to establish a correct diagnosis, especially at an early stage. As a result, the true prevalence of the pathology remains unknown. There is no treatment protocol for APDS, and drug therapy is primarily focused on treating symptoms. The most common therapies include immunoglobulin replacement therapy, antimicrobial prophylaxis, and immunosuppressive drugs. Hematopoietic stem cell transplantation (HSCT) has been used in some cases, but the risk-benefit balance remains unclear. With the upcoming introduction of specific medications, such as selective inhibitors for PI3Kδ, clinicians are shifting their attention towards target therapy. This review provides a comprehensive overview of APDS with a focus on diagnostic and treatments procedures available. This review may be useful in implementing strategies for a more efficient patients' management and therapeutic interventions. Main Text.